Composite negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202610793942.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]本发明的目的在于:提供一种复合负极材料及其制备方法和应用,用于解决气相沉积硅碳负极材料中因不可逆锂消耗和SiC生成所导致的首效低、循环寿命短的问题,以实现高首效、低体积膨胀和长循环寿命的效果
本发明通过在纳米硅层与无定形碳层之间引入化学性质极其稳定的氮化硅层,该层作为高效的“扩散阻挡层”,在热力学与动力学上有效阻止了硅原子与碳原子的相互扩散,从根本上避免了电化学惰性SiC相的生成,保证了界面纯净,从而显著提升了材料的循环可逆性与容量发挥。
Smart Images

Figure CN122907606A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials technology, and particularly relates to a composite anode material, its preparation method, and its application. Background Technology
[0002] With the rapid development of electric vehicles, high-end consumer electronics, and other fields, the requirements for the energy density of lithium-ion batteries continue to increase. Silicon (Si), with its theoretical specific capacity of up to 4200 mAh / g (approximately 10 times that of traditional graphite anodes), is considered a strong candidate for the next generation of high-capacity anode materials. However, silicon undergoes a massive volume expansion of over 300% during charge and discharge, leading to problems such as active particle pulverization, repeated rupture and regeneration of the solid electrolyte interface film, and electrical contact failure, which seriously affect the cycle life of the battery.
[0003] To address this challenge, silicon-carbon composite materials prepared by chemical vapor deposition (CVD) have become the mainstream technological approach. This technique deposits nano-silicon within a porous carbon framework, utilizing the dispersion and containment capabilities of the carbon framework and the reserved space to buffer the volume expansion of silicon. Currently, commercially available CVD silicon-carbon materials can achieve capacities of 1800–2100 mAh / g, with an initial efficiency of 91%–94%. However, this technological approach still faces two major core problems: Irreversible lithium loss problem: The porous carbon framework contains a large number of oxygen-containing functional groups (such as -COOH, -OH), which will undergo irreversible side reactions with lithium ions during the first charge and discharge process, permanently consuming active lithium, which is a key factor limiting further improvement of the first efficiency.
[0004] Silicon carbide formation problem: Under high temperature conditions, silicon and carbon skeletons easily react to form silicon carbide (SiC). SiC is an electrochemically inert material, does not store lithium and has poor conductivity, which leads to continuous capacity decay during long-term cycling.
[0005] Therefore, developing a composite anode material that can reduce irreversible lithium loss and suppress SiC formation from the material source has significant industrial value. Summary of the Invention
[0006] The purpose of this invention is to provide a composite anode material, its preparation method, and its application, to solve the problems of low initial efficiency and short cycle life caused by irreversible lithium consumption and SiC formation in vapor-deposited silicon-carbon anode materials, so as to achieve high initial efficiency, low volume expansion, and long cycle life.
[0007] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a composite negative electrode material, comprising: A porous carbon framework core; and a composite coating layer covering the surface of the porous carbon framework core; The composite coating layer comprises n deposition units arranged sequentially from the inside out, where n ≥ 1 and is an integer; Each of the deposition units includes a nano-silicon layer, a first silicon nitride layer and an amorphous carbon layer arranged sequentially. When n>1, a second silicon nitride layer is provided between two adjacent deposition units; and the outermost layer of the composite coating layer is the amorphous carbon layer.
[0008] Preferably, the porous carbon framework has a pore volume of 0.65~1.15 cc / g and a pore size of 0.7~3nm.
[0009] Preferably, the thickness of the nano-silicon layer is 5~50nm, the thickness of the first silicon nitride layer and the second silicon nitride layer is 2~10nm, and the thickness of the amorphous carbon layer is 10~100nm.
[0010] Preferably, the specific surface area of the composite negative electrode material is 0.8~2.8m². 2 / g, median particle size D50 is 4.0~12μm, true density is 1.95~2.2g / cm³ 3 The conductivity is 0.03~0.28 S / cm at a pressure of 10 MPa.
[0011] Secondly, the present invention provides a method for preparing a composite negative electrode material, comprising the following steps: S1. Pretreatment of porous carbon framework: The porous carbon material is heat-treated in a reducing atmosphere; S2, Nano-silicon deposition: The pretreated porous carbon skeleton is placed in a chemical vapor deposition reactor, and silicon source gas is introduced to deposit a nano-silicon layer on the surface of the carbon skeleton. S3. Silicon nitride layer deposition: A silicon nitride layer is formed in an atmosphere containing silicon and nitrogen by plasma chemical vapor deposition. S4. Amorphous carbon layer deposition: A carbon source gas is introduced into the surface of the silicon nitride layer, and an amorphous carbon layer is formed by chemical vapor deposition. The composite coating layer is formed by repeatedly executing steps S2 to S4. When the number of cycles is greater than 1, a step S3 is added after completing step S4 and before proceeding to the next step S2 to deposit a second silicon nitride layer on the surface of the amorphous carbon layer.
[0012] Preferably, the reducing atmosphere in step S1 is selected from at least one of hydrogen, ammonia, and carbon monoxide, the heat treatment temperature is 450~650℃, the heat treatment time is 1~6 hours, the heating rate is 2~8°C / min, and the gas flow rate is 100~300 sccm.
[0013] Preferably, the silicon source gas in step S2 is silane or chlorosilane, the deposition temperature is 400~550℃, the deposition pressure is 100~500Pa, and the deposition time is 0.5~2h.
[0014] Preferably, in step S2, the silicon source gas is diluted with a dilution gas to a volume concentration of 2% to 5%, the total flow rate of the silicon source gas and the dilution gas is 100 to 300 sccm, and the flow rate ratio of the silicon source gas to the dilution gas is 1:30 to 1:50; wherein, the dilution gas includes hydrogen with a volume concentration of 1 to 5% and argon with a volume concentration of 95 to 99%.
[0015] Preferably, the silicon-containing precursor in step S3 is silane or chlorosilane, the nitrogen-containing precursor is ammonia or nitrogen, the deposition temperature is 400~600℃, the deposition pressure is 100~500Pa, the deposition time is 30~90min, and the plasma power is 50~200W.
[0016] Preferably, in step S3, the total gas flow rate of the silicon-containing precursor and the nitrogen-containing precursor is 200~500 sccm, the gas flow rate ratio of the silicon-containing precursor to the nitrogen-containing precursor is 1:3~1:5, and the gases of the silicon-containing precursor and the nitrogen-containing precursor are diluted by a dilution gas, the flow rate of which accounts for 70~85% of the total gas flow rate.
[0017] Preferably, the carbon source gas in step S4 is selected from at least one of methane, acetylene, ethylene, and benzene, the deposition temperature is 450~550℃, and the deposition pressure is 10. 3 ~10 4 Pa, deposition time is 0.5~1.5h.
[0018] Preferably, in step S4, the carbon source gas is diluted with a dilution gas to a volume concentration of 10% to 20%, the total flow rate of the carbon source gas and the dilution gas is 100 to 300 sccm, and the flow rate ratio of the carbon source gas to the dilution gas is 1:5 to 1:10.
[0019] Thirdly, the present invention provides a negative electrode sheet comprising the above-mentioned composite negative electrode material, or comprising the composite negative electrode material prepared by the above-mentioned preparation method.
[0020] Fourthly, the present invention provides a secondary battery comprising the aforementioned negative electrode sheet.
[0021] Compared with the prior art, the present invention has at least the following beneficial effects: This invention introduces a chemically stable silicon nitride layer between a nano-silicon layer and an amorphous carbon layer. This layer acts as a highly efficient "diffusion barrier layer," effectively preventing the mutual diffusion of silicon and carbon atoms thermodynamically and kinetically. This fundamentally avoids the formation of an electrochemically inert SiC phase, ensuring interface purity and thus significantly improving the material's cycle reversibility and capacity utilization.
[0022] This invention achieves effective management of silicon volume expansion through a multi-layered structural design: First, it utilizes the internal space of a high-porosity (0.65~1.15 cc / g) porous carbon framework to provide ample intracavitary buffer space for silicon expansion; second, it employs an ultrathin, high-modulus silicon nitride layer as a rigid "nano-armor" to limit the anisotropy of silicon expansion and prevent particle breakage and agglomeration; third, it uses an amorphous carbon layer as a flexible "elastic bandage" to maintain electrical contact between electrode particles and the integrity of the overall structure. The synergistic effect of these three elements significantly reduces the electrode volume expansion rate and substantially improves the stability of the cycling structure.
[0023] The silicon nitride layer of this invention has stable chemical properties, which can guide the uniform deposition of lithium ions and reduce interfacial impedance. At the same time, this layer, together with the amorphous carbon layer, forms a physical isolation barrier, completely separating the internal silicon from the electrolyte, fundamentally preventing the repeated rupture and regeneration of the SEI film on the silicon surface, significantly reducing irreversible active lithium consumption, thereby simultaneously improving the initial coulombic efficiency and long-term cycle stability.
[0024] This invention forms a dual conductive structure of "silicon nitride layer + amorphous carbon layer," which can still provide an efficient electron transport channel for each active silicon site under deep charge-discharge and large volume changes. By controlling the thickness and crystallinity of the amorphous carbon, good ion permeability can be maintained while ensuring mechanical strength, promoting the rapid entry of lithium ions into the material, thereby effectively improving the fast-charging capability of the battery. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a scanning electron microscope image of the composite negative electrode material of the present invention; Figure 2 This is a transmission electron microscope (TEM) image of the composite negative electrode material of this invention. Detailed Implementation
[0027] To make the technical problem to be solved, the technical solution, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.
[0028] In this invention, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0029] In this invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0030] It should be understood that in various embodiments of the present invention, the order of the above-mentioned processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0031] According to a first aspect of the present invention, the present invention provides a composite anode material, comprising: A porous carbon framework core; and a composite coating layer covering the surface of the porous carbon framework core; The composite coating layer comprises n deposition units arranged sequentially from the inside out, where n ≥ 1 and is an integer; Each of the deposition units includes a nano-silicon layer, a first silicon nitride layer and an amorphous carbon layer arranged sequentially. When n>1, a second silicon nitride layer is provided between two adjacent deposition units; and the outermost layer of the composite coating layer is the amorphous carbon layer.
[0032] In some embodiments of the present invention, the porous carbon framework has a pore volume of 0.65~1.15 cc / g and a pore size of 0.7~3 nm. For example, the pore volume of the porous carbon framework can be 0.65cc / g, 0.75cc / g, 0.85cc / g, 0.95cc / g, 1.05cc / g, 1.15 cc / g, etc., and the pore size can be 0.7nm, 1nm, 1.2nm, 1.5nm, 1.7nm, 2nm, 2.2nm, 2.5nm, 2.7nm, 3nm, etc.
[0033] The high pore volume of 0.65~1.15 cc / g ensures sufficient porosity to achieve the silicon loading required for high capacity, while avoiding stress concentration due to excessive silicon filling that could cause carbon skeleton breakage. The pore size (0.7~3nm) effectively confines and anchors the subsequently chemically vapor-deposited silicon nanoparticles through capillary effect, preventing them from agglomerating or detaching during cycling, while also reserving sufficient internal buffer space for silicon volume expansion. Too narrow a pore size (<0.7nm) is not conducive to the uniform diffusion and penetration of silane gas molecules, and is prone to surface deposition that blocks the pore openings, while too large a pore size (>3nm) may weaken the dispersion and confinement of silicon nanoparticles and accelerate their electrochemical sintering.
[0034] In some embodiments of the present invention, the thickness of the nano-silicon layer is 5-50 nm, the thickness of both the first silicon nitride layer and the second silicon nitride layer is 2-10 nm, and the thickness of the amorphous carbon layer is 10-100 nm. For example, the thickness of the nano-silicon layer can be 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc., the thickness of the silicon nitride layer can be 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, etc., and the thickness of the amorphous carbon layer can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0035] In some embodiments of the present invention, the specific surface area of the composite negative electrode material is 0.8~2.8m². 2 / g, median particle size D50 is 4.0~12μm, true density is 1.95~2.2g / cm³ 3 The conductivity is 0.03~0.28 S / cm at a pressure of 10 MPa.
[0036] According to a second aspect of the present invention, the present invention provides a method for preparing a composite negative electrode material, comprising the following steps: S1. Pretreatment of porous carbon framework: The porous carbon material is heat-treated in a reducing atmosphere; S2, Nano-silicon deposition: The pretreated porous carbon skeleton is placed in a chemical vapor deposition reactor, and silicon source gas is introduced to deposit a nano-silicon layer on the surface of the carbon skeleton. S3. Silicon nitride layer deposition: A silicon nitride layer is formed in an atmosphere containing silicon and nitrogen by plasma chemical vapor deposition. S4. Amorphous carbon layer deposition: A carbon source gas is introduced into the surface of the silicon nitride layer, and an amorphous carbon layer is formed by chemical vapor deposition. The composite coating layer is formed by repeatedly executing steps S2 to S4. When the number of cycles is greater than 1, a step S3 is added after completing step S4 and before proceeding to the next step S2 to deposit a second silicon nitride layer on the surface of the amorphous carbon layer.
[0037] The process involves alternating deposition steps S2-S4, culminating in the deposition and encapsulation of an amorphous carbon layer until the pores of the porous carbon framework are filled. This structure aims to isolate silicon clusters using an ultrathin carbon layer, buffering their expansion stress and maintaining the conductive network. The three-layer structure—"nano-silicon layer + silicon nitride layer + amorphous carbon layer"—aims to simultaneously address the three major challenges of silicon volume expansion, electrical contact, and direct reaction with carbon (to form SiC). The silicon nitride layer is used as an "isolation layer." The principle is that after silicon deposition, a dense silicon nitride layer is immediately coated onto the silicon surface. Subsequent carbon deposition (even at higher temperatures) occurs on the silicon nitride layer surface, not the silicon surface, thus physically blocking the path of direct contact and reaction between silicon and carbon sources (such as acetylene) at high temperatures. The low-temperature and plasma-activated process is adopted because: it is essential to ensure that the silicon nitride layer deposition temperature (400-600℃) is much lower than the temperature at which silicon and carbon can react significantly (usually >600℃); the "plasma-activated N2 / H2" is chosen because plasma can dissociate nitrogen molecules into active nitrogen atoms, allowing them to react and generate silicon nitride at low temperatures, which is the key to achieving low-temperature, high-quality film formation.
[0038] In some embodiments of the present invention, the reducing atmosphere in step S1 is selected from at least one of hydrogen, ammonia, and carbon monoxide, the heat treatment temperature is 450~650°C, the heat treatment time is 1~6 hours, the heating rate is 2~8°C / min, and the gas flow rate is 100~300 sccm.
[0039] In step S1, carbon monoxide, acting as a reducing atmosphere, reacts with oxygen-containing groups in the porous carbon framework to generate carbon dioxide, achieving deep deoxygenation. Simultaneously, the generated carbon dioxide performs secondary etching on the carbon wall, introducing nanoscale defects and micropores, further increasing the specific surface area and active sites.
[0040] In some embodiments of the present invention, the silicon source gas in step S2 is silane or chlorosilane, the deposition temperature is 400~550℃, the deposition pressure is 100~500Pa, and the deposition time is 0.5~2h.
[0041] In some embodiments of the present invention, the silicon source gas in step S2 is diluted with a dilution gas to a volume concentration of 2% to 5%, the total flow rate of the silicon source gas and the dilution gas is 100 to 300 sccm, and the flow rate ratio of the silicon source gas to the dilution gas is 1:30 to 1:50; wherein, the dilution gas includes hydrogen with a volume concentration of 1 to 5% and argon with a volume concentration of 95 to 99%.
[0042] To achieve uniform silicon deposition on the inner and outer surfaces of porous carbon and avoid reaction with the carbon substrate, plasma-enhanced chemical vapor deposition (PECVD) is employed. Highly reactive silanes or chlorosilanes are used as the silicon source gas, while high-purity hydrogen and argon are used as dilution gases. Hydrogen helps clean the surface and inhibits gas-phase nucleation, but its dosage must be controlled to prevent trace reduction of the carbon substrate. Step S2 is crucial in strictly controlling the deposition temperature between 400°C and 550°C (typically below the significant silicon-carbon reaction initiation temperature of 550°C) and maintaining a low-pressure environment of 100–500 Pa to promote gas diffusion within the micropores. The concentration of the silicon source gas should be 2%–5% (volume fraction), mixed with the dilution gas (a mixture of Ar and 1%–5% H2) at a dilution ratio of 1:30–1:50. The total gas flow rate is controlled at 100–300 sccm to ensure stable powder fluidization. The deposition time is set to 0.5–2 h depending on the target silicon loading. By taking the above measures, premature clogging of the pores can be effectively prevented, and uniform and controllable deposition of silicon nanoparticles or thin layers in carbon channels can be achieved.
[0043] In some embodiments of the present invention, the silicon-containing precursor in step S3 is silane or chlorosilane, the nitrogen-containing precursor is ammonia or nitrogen, the deposition temperature is 400~600℃, the deposition pressure is 100~500Pa, the deposition time is 30~90min, and the plasma power is 50~200W.
[0044] In some embodiments of the present invention, the total gas flow rate of the silicon-containing precursor and the nitrogen-containing precursor in step S3 is 200~500 sccm, the gas flow rate ratio of the silicon-containing precursor to the nitrogen-containing precursor is 1:3~1:5, and the gases of the silicon-containing precursor and the nitrogen-containing precursor are diluted by a dilution gas, the flow rate of the dilution gas accounting for 70~85% of the total gas flow rate.
[0045] To achieve uniform coating of pre-deposited silicon particles within porous carbon and construct a dense, continuous, and conductive silicon nitride layer (target thickness 2-10 nm) to isolate the contact reaction between silicon and carbon during subsequent carbon deposition, plasma-enhanced atomic layer deposition (PEALD) is employed. This method enables conformal, nanoscale precision control of film growth, making it particularly suitable for complex surfaces within porous materials. Silane or chlorosilane are used as silicon precursors, while ammonia or plasma-activated nitrogen is used as the nitrogen precursor. Silane provides the silicon source, and ammonia provides the nitrogen source, introduced in a 1:3 to 1:5 ratio to ensure nitrogen excess, forming stoichiometric silicon nitride and avoiding the formation of a silicon-rich phase. During deposition, a dilution gas (such as Ar or an Ar mixture containing 1%-5% H2) comprising 70%-85% of the total gas volume is added to promote uniform diffusion of the silicon and nitrogen precursors into the porous carbon. The total gas flow rate is controlled at 200-500 sccm to ensure the powder remains in a stable fluidized state. The deposition temperature was maintained between 400 and 600°C. This range ensures film quality (too low a temperature results in poor film density, while too high a temperature may induce silicon-carbon reactions) without damaging the deposited silicon structure. The plasma power was set to 50–200 W to excite precursor decomposition and promote Si-N bond formation. The deposition pressure was maintained at a low pressure environment of 100–500 Pa, which facilitates sufficient gas diffusion within the micropores. The deposition time was set to 30–90 min depending on the target thickness (5–20 nm). Through these optimized parameters, a pinhole-free, highly dense silicon nitride layer can be formed on the silicon surface inside porous carbon, effectively acting as a "Great Wall" between silicon and carbon.
[0046] In some embodiments of the present invention, the carbon source gas in step S4 is selected from at least one of methane, acetylene, ethylene, and benzene, the deposition temperature is 450~550°C, and the deposition pressure is 10. 3 ~10 4 Pa, deposition time is 0.5~1.5h.
[0047] In some embodiments of the present invention, the carbon source gas in step S4 is diluted with a dilution gas to a volume concentration of 10% to 20%, the total flow rate of the carbon source gas and the dilution gas is 100 to 300 sccm, and the flow rate ratio of the carbon source gas to the dilution gas is 1:5 to 1:10.
[0048] After constructing the silicon nitride layer, to further provide a conductive network, mechanical constraint, and buffer the volume expansion of silicon during cycling, an amorphous carbon layer needs to be deposited on the surface of the porous carbon-silicon-silicon nitride composite structure to stabilize the overall electrode structure. Chemical vapor deposition (CVD) is used, with acetylene as the carbon source gas due to its moderate pyrolysis temperature and abundant carbon source. Crucially, at this stage, the silicon nitride layer completely covers the silicon surface and can withstand higher temperatures than the initial silicon deposition, thus obtaining a higher quality carbon layer. However, temperature control is still necessary to avoid damage to the silicon nitride layer or excessive graphitization and brittleness of the carbon layer. The acetylene concentration is 10%–20% (volume fraction), diluted with Ar or H2. The gas flow ratio of acetylene to dilution gas (Ar mixture containing 1%–5% H2) is set to 1:5–1:10 to ensure a dense carbon layer while maintaining the deposition rate. The total gas flow rate is controlled at 100–300 sccm to maintain a stable fluidization state. The deposition temperature is set to 450°C~550°C. This temperature range allows acetylene to fully decompose and form amorphous carbon with excellent conductivity. Simultaneously, due to the protective effect of the silicon nitride layer, silicon does not directly contact carbon, fundamentally preventing the formation of silicon carbide. The deposition pressure can be atmospheric pressure or low pressure (10... 3 ~10 4 Atmospheric pressure chemical vapor deposition (CVD) is simpler to operate and suitable for large-scale production. The deposition time is set to 0.5~1.5 h depending on the required carbon layer thickness—too short a time will result in insufficient protection, while too long a time will increase interfacial impedance and reduce the energy density of the electrode. Through the above optimization conditions, an amorphous carbon layer with both conductivity and flexibility can be formed on the surface of the composite structure, further enhancing the structural stability and electrochemical performance of the electrode.
[0049] According to a third aspect of the present invention, the present invention provides a negative electrode sheet comprising the above-described composite negative electrode material, or comprising the composite negative electrode material prepared by the above-described preparation method.
[0050] According to a fourth aspect of the present invention, a secondary battery is provided, comprising the above-described negative electrode sheet.
[0051] According to a fifth aspect of the present invention, a method for preparing a secondary battery is provided, comprising the following steps: The conductive agent is premixed with the negative electrode material, wherein the negative electrode material is a combination of artificial graphite negative electrode material and composite negative electrode material; first, 30-70% binder and solvent are added and mixed and kneaded for 0.5-3 hours; then 15-35% binder, the remaining conductive agent and solvent are added and mixed and stirred for 0.5-3 hours, controlling the solid content at 30-55%; finally, the remaining binder and solvent are added and stirred, controlling the solid content at 25-48% and the fineness ≤45μm, to obtain the negative electrode slurry; The conductive agent and the positive electrode material are premixed. First, 30-70% of the binder and solvent are added and kneaded for 0.5-3 hours. Then, the remaining binder, conductive agent, solvent and electrolyte are added and mixed and stirred for 0.5-3 hours, controlling the solid content to 65-85%. Finally, the solvent is added and stirred for 0.5-3 hours, controlling the solid content to 60-80% and the fineness to ≤45μm, to obtain the positive electrode slurry. The negative electrode slurry is coated onto a foil, with the areal density controlled to be 0.003~0.015 g / cm³. 2 After drying to remove solvent, rolling, cutting, drying and die-cutting, negative electrode sheets are obtained; The positive electrode slurry is coated onto a foil, with the areal density controlled to be 0.012~0.027 g / cm³. 2 After drying to remove solvent, rolling, drying, and die-cutting, positive electrode sheets are obtained. The positive electrode, separator, and negative electrode are stacked in sequence, and then tabs are welded, casing is installed, electrolyte is injected, formation is performed, and capacity is tested to obtain a secondary battery.
[0052] In some embodiments of the present invention, the composite anode material is the composite anode material described above, or includes the composite anode material prepared by the above preparation method.
[0053] In some embodiments of the present invention, the conductive agent is selected from at least one of conductive carbon black, conductive Ketjen black, conductive acetylene black, conductive graphene, single-walled carbon nanotubes, multi-walled carbon nanotubes, and oligo-walled carbon nanotubes.
[0054] In some embodiments of the present invention, the adhesive is selected from at least one of lithium polyacrylate, polymethyl methacrylate, polyethyl ethyl acrylate, lithium polyacrylate-methacrylate, sodium polyacrylate / lithium-acrylonitrile, carboxymethyl cellulose, and polyvinylidene fluoride.
[0055] In some embodiments of the present invention, the electrolyte is selected from at least one of lithium lanthanum zirconate, lithium lanthanum tantalate, lithium lanthanum zirconate tantalate, lithium titanium aluminum phosphate, lithium germanium aluminum phosphate, polyoxyethylene, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethyl methacrylate, lithium indium chloride, lithium indium bromide, lithium yttrium chloride, lithium yttrium bromide, lithium chlorine-sulfur-phosphorus, and lithium sulfur-phosphorus-germanium.
[0056] In some embodiments of the present invention, the positive electrode material is selected from at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium-rich manganese-based oxide, lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel manganese oxide.
[0057] In some embodiments of the present invention, the areal density of the negative electrode slurry coated on the foil is 3.2~17 mg / cm³. 2The areal density of the positive electrode slurry coated on the foil is 12~56 mg / cm³. 2 .
[0058] In some embodiments of the present invention, the thickness of the negative electrode sheet is 45~195 μm; In some embodiments of the present invention, the mass ratio of negative electrode material, conductive agent and binder in the negative electrode slurry is (90~98.6):(0.2~10):(1.2~8).
[0059] In some embodiments of the present invention, the mass ratio of positive electrode material, conductive agent, binder and electrolyte in the positive electrode slurry is (90~99.3):(0.05~6):(0.6~10):(0.02~0.8).
[0060] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0061] Example 1
[0062] Preparation of negative electrode I. Selection and Pretreatment of Porous Carbon Frameworks Spherical porous carbon material with a D50 of 8 μm was selected, with pore sizes concentrated between 0.7 and 3 nm, a microporosity of 92%, and a total pore volume of 0.95 cc / g. The porous carbon material was placed in a tube furnace and heated to 550°C at a rate of 5°C / min under argon protection. CO was then introduced at a flow rate of 100 sccm, and the temperature was maintained for 2 hours for deep deoxidation and secondary etching. After the reaction, the material was cooled to room temperature under argon protection to obtain the pretreated porous carbon framework. Testing showed that the specific surface area of the treated porous carbon framework increased from 1120 m² / g. 2 / g increased to 1370m 2 / g, the number of oxygen-containing functional groups on the surface is significantly reduced.
[0063] II. Alternating deposition of silicon / silicon nitride / carbon Using a plasma-enhanced vapor deposition (PEVDC) system, the following steps were followed for 10 cycles of deposition, culminating in an amorphous carbon layer encapsulation: S1. Nano-silicon deposition: Silane was used as the silicon source gas (concentration of 3 vol%, diluted with Ar), the gas flow ratio was 1:35, the total flow rate was 200 sccm, the deposition temperature was 450°C, the pressure was 400 Pa, and the deposition time was 45 min. S2. Silicon nitride layer deposition: Silane and ammonia are used as precursors, the gas flow ratio is 1:3, Ar dilution gas accounts for 75% of the total gas flow, the total flow is 400 sccm, the deposition temperature is 450°C, the plasma power is 100W, the pressure is 200Pa, the deposition time is 60min, and the target thickness is 8nm. S3. Amorphous carbon layer deposition: Acetylene was used as the carbon source gas (concentration 15 vol%), the gas flow ratio was 1:8, the total flow rate was 200 sccm, the deposition temperature was 510°C, and the pressure was atmospheric (1×10⁻⁶). 5 Deposition at Pa) for 50 min; After completing step S3 and before proceeding to the next step S1, an additional step S2 is added to deposit a second silicon nitride layer on the surface of the amorphous carbon layer; after completing the alternating deposition, a composite anode material is obtained.
[0064] III. Preparation of Negative Electrode Sheets Composite anode material, artificial graphite, conductive carbon black, single-walled carbon nanotubes, lithium polyacrylate, and carboxymethyl cellulose were mixed in a mass ratio of 20:72:2:0.3:4:1.7. Deionized water was added to form a slurry, which was stirred for 4 hours and then uniformly coated onto the surface of copper foil. The areal density of the anode was controlled to be 8.5 mg / cm³. 2 After being dried with hot air at 85°C, it is rolled to a density of 1.55 g / cm³. 3 After being vacuum dried at 120°C for 12 hours, the negative electrode sheet is finally obtained by die cutting.
[0065] Example 2
[0066] Unlike Example 1, the time for silicon nitride layer deposition in step two is increased to 70 minutes, while the remaining steps are the same as in Example 1.
[0067] Example 3
[0068] Unlike Example 1, the temperature for amorphous carbon layer deposition in step two is increased to 550°C, while the remaining steps are the same as in Example 1.
[0069] Example 4
[0070] Unlike Example 1, the number of cycles in step two is increased to 15, while the remaining steps are the same as in Example 1.
[0071] Example 5
[0072] Unlike Example 1, in step two, the nano-silicon deposition uses chlorosilane as the silicon source gas, and the silicon nitride layer deposition uses chlorosilane and nitrogen as precursors. The remaining steps are the same as in Example 1.
[0073] Example 6
[0074] Unlike Example 1, in step one the microporosity of the porous carbon material is increased to 98% and the total pore volume is increased to 1.08 cc / g. The remaining steps are the same as in Example 1.
[0075] Comparative Example 1 Unlike Example 1, the porous carbon material is not pretreated in step one, while the remaining steps are the same as in Example 1.
[0076] Comparative Example 2 Unlike Example 1, silicon nitride layer deposition is not performed in step two; the remaining steps are the same as in Example 1.
[0077] Comparative Example 3 Unlike Example 1, step two does not involve the deposition of an amorphous carbon layer; the remaining steps are the same as in Example 1.
[0078] Comparative Example 4 Unlike Example 1, the temperature for nano-silicon deposition in step two is increased to 650°C, while the remaining steps are the same as in Example 1.
[0079] Comparative Example 5 Unlike Example 1, the temperature for silicon nitride deposition in step two is increased to 650°C, while the remaining steps are the same as in Example 1.
[0080] Comparative Example 6 Unlike Example 1, the temperature for amorphous carbon layer deposition in step two is increased to 600°C, while the remaining steps are the same as in Example 1.
[0081] The negative electrode sheets obtained in the above embodiments and Comparative Example 1 were used to fabricate secondary batteries and their performance was tested. The test results are shown in Table 1.
[0082] First-cycle coulomb efficiency test: The first charge-discharge test is conducted at a rate of 0.1C, and the ratio of the first discharge capacity to the first charge capacity is calculated.
[0083] Expansion rate test: Using an in-situ thickness measuring instrument or battery micrometer, the thickness change of the electrode sheet in the fully lithium-intercalated state and the fully lithium-deintercalated state is measured, and the volume expansion rate is calculated.
[0084] Cyclic testing: The test was conducted indoors at a temperature of 25±1℃ and a relative humidity of less than 65%, with the battery held without clamps. Charge / discharge procedure (each cycle is performed sequentially): Charge at a constant current of 3.0C to 4.05V, rest for 300 seconds; charge at a constant current of 2.9C to 4.15V, rest for 300 seconds; charge at a constant voltage of 4.15V until the current drops to 2.30C, rest for 300 seconds; charge at a constant current of 2.50C to 4.25V, rest for 300 seconds; charge at a constant voltage of 4.25V until the current drops to... 1.80C, rest for 300 seconds; charge at a constant current of 2.0C to 4.40V, rest for 300 seconds; charge at a constant voltage of 4.40V until the current drops to 1.55C, rest for 300 seconds; charge at a constant current of 1.55C to 4.50V, rest for 300 seconds; charge at a constant voltage of 4.50V until the current drops to 1.20C, rest for 300 seconds; discharge at a constant current of 0.5C to 3.0V. After completion, the next cycle returns to the initial state. The recording and termination condition is the discharge capacity measured in the last step of the first cycle (0.5C discharge), denoted as C. 0.5 Continue the above cycle until the 0.5C discharge capacity in the last step of a certain cycle decreases to the initial C value. 0.5 When the battery capacity drops to 80% (i.e., decays to 80% of its initial capacity), the test is stopped; the number of charge-discharge cycles that the battery has completed at this point is recorded as its cycle life.
[0085] Rate performance testing: Measure the battery capacity at discharge rates of 0.2C, 0.5C, 1.0C, and 2.0C, and calculate the ratio of each rate to the 0.2C capacity. The test procedure (performed sequentially without overlap) is as follows: Measure the 0.2C discharge capacity R... 0.2 First, charge at a constant current of 0.5C to 4.5V, then charge at a constant voltage until the current drops to 0.25C, and let stand for 300 seconds; then discharge at a constant current of 0.2C to 3.0V, and let stand for 300 seconds; record the discharge capacity at this time as R. 0.2 Measure the 0.5C discharge capacity R 0.5 Similarly, charge at a constant current of 0.5C to 4.5V, then maintain a constant voltage of 0.25C, and let stand for 300 seconds; discharge at a constant current of 0.5C to 3.0V, and let stand for 300 seconds; record the discharge capacity at this time as R. 0.5 Measure the 1.0C discharge capacity R 1.0 First, apply a constant current of 0.5C to 4.5V, then a constant voltage of 0.25C, and let it stand for 300 seconds; then discharge at a constant current of 1.0C to 3.0V, and let it stand for 300 seconds; the recording capacity is R. 1.0 Measure the 2.0C discharge capacity R 2.0First, apply a constant current of 0.5C to 4.5V, then a constant voltage of 0.25C, and let it stand for 300 seconds; then discharge at a constant current of 2.0C to 3.0V, and let it stand for 300 seconds; the recording capacity is R2.0. Rate performance calculation: 0.5C rate = R 0.5 / R 0.2 ; 1.0C ratio = R 1.0 / R 0.2 ; 2.0C ratio = R 2.0 / R 0.2 .
[0086] Table 1 From Table 1, we can obtain: Examples 1-3 and 5 show that, within the appropriate deposition time and temperature range (Examples 1, 2, and 3) and by selecting suitable raw materials, the battery's initial efficiency, expansion rate, cycle performance, and rate performance are all superior to the comparative example; indicating that optimizing deposition process parameters can effectively improve the overall performance of the battery.
[0087] Based on Examples 1 and 4, Example 4 showed a slightly lower initial efficiency (92.8% vs 93.6%) and a slightly higher expansion rate (19.5% vs 18.4%), but a longer cycle life (1100 cycles vs 930 cycles). This indicates that increasing the cycle deposition period can balance the relationship between initial efficiency, expansion, and lifespan, and can be selected according to the target focus.
[0088] Based on Examples 1 and 6, Example 6 is superior to Example 1 in terms of first-time efficiency (95.1%), expansion rate (15.8%), cycle life (1080 cycles), and rate capability (0.5C: 98%, 2.0C: 89%). This indicates that appropriately increasing or optimizing the microporosity and pore volume of porous carbon materials helps to improve capacity retention and rate capability while suppressing expansion.
[0089] Based on Examples 1 and Comparative Examples 1-3, it can be seen that the first-time efficiency (88.5%~90.1%) of Comparative Examples 1-3 (without porous carbon framework pretreatment or without silicon nitride layer or amorphous carbon layer deposition) is significantly lower than that of Example 1 (93.6%), the expansion rate (26.8%~31.2%) is significantly increased, the cycle life (620~700 cycles) is significantly reduced, and the electrode shows cracks or local detachment; indicating that pretreatment and deposition processes are key steps to ensure electrode integrity and electrochemical performance.
[0090] Based on Example 1 and Comparative Examples 4-6, it can be seen that Comparative Examples 4-6 (with excessively high deposition temperature) have reduced initial efficiency, increased expansion rate, decreased cycle life, local or large-area electrode detachment, and significantly reduced rate performance. This indicates that excessively high deposition temperature can seriously damage the electrode structure and battery performance, and must be controlled within a suitable range.
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A composite negative electrode material, characterized in that, include: Porous carbon framework core; And a composite coating layer covering the surface of the porous carbon framework core; The composite coating layer comprises n deposition units arranged sequentially from the inside out, where n ≥ 1 and is an integer; Each of the deposition units includes a nano-silicon layer, a first silicon nitride layer and an amorphous carbon layer arranged sequentially. When n>1, a second silicon nitride layer is provided between two adjacent deposition units; and the outermost layer of the composite coating layer is the amorphous carbon layer.
2. The composite negative electrode material according to claim 1, characterized in that, The porous carbon framework has a pore volume of 0.65~1.15 cc / g and a pore size of 0.7~3nm.
3. The composite negative electrode material according to claim 1, characterized in that, The thickness of the nano-silicon layer is 5~50nm, the thickness of the first silicon nitride layer and the second silicon nitride layer is 2~10nm, and the thickness of the amorphous carbon layer is 10~100nm.
4. The composite negative electrode material according to claim 1, characterized in that, The specific surface area of the composite negative electrode material is 0.8~2.8m². 2 / g, median particle size D50 is 4.0~12μm, true density is 1.95~2.2g / cm³ 3 The conductivity is 0.03~0.28 S / cm at a pressure of 10 MPa.
5. A method for preparing the composite negative electrode material according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1. Pretreatment of porous carbon framework: The porous carbon material is heat-treated in a reducing atmosphere; S2, Nano-silicon deposition: The pretreated porous carbon skeleton is placed in a chemical vapor deposition reactor, and silicon source gas is introduced to deposit a nano-silicon layer on the surface of the carbon skeleton. S3. Silicon nitride layer deposition: A silicon nitride layer is formed in an atmosphere containing silicon and nitrogen by plasma chemical vapor deposition. S4. Amorphous carbon layer deposition: A carbon source gas is introduced into the surface of the silicon nitride layer, and an amorphous carbon layer is formed by chemical vapor deposition. The composite coating layer is formed by repeatedly executing steps S2 to S4. When the number of cycles is greater than 1, a step S3 is added after completing step S4 and before proceeding to the next step S2 to deposit a second silicon nitride layer on the surface of the amorphous carbon layer.
6. The preparation method according to claim 5, characterized in that, The reducing atmosphere in step S1 is selected from at least one of hydrogen, ammonia, and carbon monoxide. The heat treatment temperature is 450~650℃, the heat treatment time is 1~6 hours, the heating rate is 2~8°C / min, and the gas flow rate is 100~300sccm.
7. The preparation method according to claim 5, characterized in that, The silicon source gas mentioned in step S2 is silane or chlorosilane, the deposition temperature is 400~550℃, the deposition pressure is 100~500Pa, and the deposition time is 0.5~2h; And / or, in step S2, the silicon source gas is diluted with a dilution gas to a volume concentration of 2% to 5%, the total flow rate of the silicon source gas and the dilution gas is 100 to 300 sccm, and the flow rate ratio of the silicon source gas to the dilution gas is 1:30 to 1:50; wherein, the dilution gas includes hydrogen with a volume concentration of 1 to 5% and argon with a volume concentration of 95 to 99%.
8. The preparation method according to claim 7, characterized in that, In step S3, the silicon-containing precursor is silane or chlorosilane, the nitrogen-containing precursor is ammonia or nitrogen, the deposition temperature is 400~600℃, the deposition pressure is 100~500Pa, the deposition time is 30~90min, and the plasma power is 50~200W. And / or, in step S3, the total gas flow rate of the silicon-containing precursor and the nitrogen-containing precursor is 200~500 sccm, the gas flow rate ratio of the silicon-containing precursor to the nitrogen-containing precursor is 1:3~1:5, and the gases of the silicon-containing precursor and the nitrogen-containing precursor are diluted by a dilution gas, the flow rate of which accounts for 70~85% of the total gas flow rate.
9. The preparation method according to claim 8, characterized in that, The carbon source gas in step S4 is selected from at least one of methane, acetylene, ethylene, and benzene, the deposition temperature is 450~550℃, and the deposition pressure is 10. 3 ~10 4 Pa, deposition time is 0.5~1.5h; And / or, in step S4, the carbon source gas is diluted with a dilution gas to a volume concentration of 10% to 20%, the total flow rate of the carbon source gas and the dilution gas is 100 to 300 sccm, and the flow rate ratio of the carbon source gas to the dilution gas is 1:5 to 1:
10.
10. A negative electrode sheet, characterized in that, The composite anode material comprising any one of claims 1 to 4, or the composite anode material prepared by any one of claims 5 to 9.
11. A secondary battery, characterized in that, It includes the negative electrode sheet as described in claim 10.